Peningkatan Profesionalitas Guru dalam Pemanfaatan Lingkungan Sekolah Sebagai Sumber Belajar melalui Diskusi Kelompok Kerja Guru (KKG) - Saidah, Ida (Universitas Pendidikan Ganesha, 2018)
From the results of observation of researchers as principals, so far the teachers at SMK Jakarta 60 have data and information that the school environment is very rarely used by teachers as a source of learning. For this reason, through guidance and discussion with the KKG about professionalism in implementing learning by utilizing the school environment as a learning resource and believed to be able to improve the quality of learning in Jakarta State Vocational High School for the field of Tourism expertise. This school action research was carried out with the aim of increasing teacher professionalism in utilizing the school environment as a learning resource. This research was designed in the form of School Action Research which was planned to be carried out in two cycles, where each cycle was carried out in two meetings. The subjects of this study were teachers at SMK Jakarta 60 which consisted of six productive teachers and two adaptive and Normative teachers. The implementation of this study begins with collecting data and using the observation format, learning scenario assessment instruments and assessment instruments for learning implementation. Furthermore, the collected data was analyzed using descriptive analysis whose results were in the first cycle the average value obtained was 79.38, while in the second cycle the average value obtained was 84.88. So that it can be concluded that coaching and guidance through the teacher working group discussion approach can improve the professionalism of teachers in the use of the school environment as a learning resource for teachers in SMK 60 Jakarta is very effective.